Post Partum Pyometra in Iraqi Goats: Clinical & Therapeutical Study - M., Al-Hamedawi T. (The Iraqi Journal of Veterinary Medicine, 2011)
Iraqi goats (27) were used in this study .They were diagnosed clinically as cases of postpartum open pyometra (external &vaginal examination ) .This study was performed in vet med /Baghdad university and two regions from Baghdad province ,their age 2-5years from 2008-2011. They were divided randomly into three groups (9goats of each group) .The 1st group treated with 250 μg of estrumate I/M injected and 2gm (10ml) oxytetracycline 20% intrauterine (I.U).The 2nd group treated with estrumate in same dose and 1tube of Metricure I.U and the 3rd group treated with estrumate and 25ml of0.5% loguls iodine . Results showed that the number of goats responded were 77.7%, 66.6%and 88.8% in the 1st ,2nd and 3rd group respectively . The mean of the days open were 43.12±9.16,148.31±8.24 and 136.42±8.51 in the 1st ,2nd and 3rd group ,1st and 2nd group were significant P<0.01 with 3rd group (decreases) .The number of newly born kids were 32 kids (17male ,15female ). The alive were 27(84.3%) and dead 5(5.7%) .The retention of fetal membrane recorded 4/21 (19.04). In conclusion that the PGF2α (estrumate) has an effect role in the treatment of pyometra in goats and its effect increasing when combined with loguls iodine or oxytetracycline.